2009
DOI: 10.1021/cg900995u
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Metal Oxalatophosphonates: Syntheses, Structure Diversity, and Photoluminescence Properties

Abstract: Hydrothermal reactions of N-piperidinomethane-1-phosphonic acid (H 2 pmp) and oxalate anion with trivalent rare earth metal ions yielded 13 rare earth oxalatophosphonates with three closely related structural types, ranging from two-dimensional (2D) networks to three-dimensional (3D) frameworks. They are formulated as [Ln 3 (Hpmp) 5), Sm (6), Eu (7), Tb (8), Dy (9), Ho (10), Er (11), Yb (12), Y (13), type II structure], andTheir structures were characterized by single crystal X-ray diffraction, powder X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 43 publications
3
13
0
Order By: Relevance
“…This is nei ther similar to other reported transition metal com plexes, in which the central ions are connected through ambient oxalate ligands to form honeycomb homometallic layers [15], nor it is different from the lanthanide complexes containing oxalatophospho nates, in which six Ln 3+ ions were linked through six oxalate anions into a netlike {Ln(C 2 O 4 ) n } 24 member ring in a layer [16]. However, when the binuclear Er 2 unit doubly connected through carboxylic group is re garded as a three connected node, the whole structure can be described as a uninodal 3 connected corrugat ed network, with 3, 6 hcb topology [17], and the point symbol is 6 3 , as shown in Fig.…”
Section: Resultssupporting
confidence: 86%
“…This is nei ther similar to other reported transition metal com plexes, in which the central ions are connected through ambient oxalate ligands to form honeycomb homometallic layers [15], nor it is different from the lanthanide complexes containing oxalatophospho nates, in which six Ln 3+ ions were linked through six oxalate anions into a netlike {Ln(C 2 O 4 ) n } 24 member ring in a layer [16]. However, when the binuclear Er 2 unit doubly connected through carboxylic group is re garded as a three connected node, the whole structure can be described as a uninodal 3 connected corrugat ed network, with 3, 6 hcb topology [17], and the point symbol is 6 3 , as shown in Fig.…”
Section: Resultssupporting
confidence: 86%
“…The concentration of precipitant solution used for conversion of the oxalates to oxides of rare earths was 80 g/mL, thus obtaining a yield of 98.25%. Oxalic acid has great selectivity, allowing for the attainment of rare earth oxalates which are insoluble in the reaction medium used [21][22][23]. According to the statistical design, we obtained oxalate by calcination from XRD pattern in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The behavior of the mixed rare earth oxide observed in the XRD pattern suggested that the constituents of the same metals, as oxides, form a solid solution of yttrium matrix due to the similarity of the rare earths (atomic radius, ionic radius, electronegativity and valence). The peaks were slightly displaced with respect to the rare earth oxides with the highest concentration found in xenotime [22][23][24][25][26]. Chemical analysis by atomic emission spectroscopy by induced plasma (Table VIII) [8].…”
Section: Resultsmentioning
confidence: 99%
“…This so called "antenna effect" has been well documented for lanthanide complexes based on β-diketonates, polyazine ligands, microcycle polyamines and aromatic carboxylate ligands [6][7][8][9][10][11][12][13][14][15][16][17][18]. Our research group has also reported some luminescent lanthanide complexes constructed from phosphonate, sulfonate, oxalate and carboxylate ligands in recent years [19][20][21]. The oxalate ligand (H 2 ox) chelates to Ln ions and forms a series of complex lanthanide oxalates, from the commonly known Ln(C 2 O 4 ) n (n = 1-4) moieties to the rarely observed Ln(C 2 O 4 ) 5 units [22,23].…”
mentioning
confidence: 76%